Reposisi Peran Fungsi Negara Dan Bisnis Dalam Rangka Pencapaian Kesejahteraan Umum - Syahrir, Azhar (DPPM UNIVERSITAS PELITA BANGSA, 2022)
Democracy and Economy are the two most basic things in determining the existence of a country in the eyes of the world. This paper contains a scientific framework to provide alternative ideas and thoughts about contemporary problems that have placed human beings not as subjects of national economic civilization but instead as economic objects in inhumane and ethical relationships. The thoughts and ideas in this paper also want to provide a scientific answer to the role of business and the state in realizing general well-being as mandated as the state's goal in the preamble of the 1945 Constitution. The method used in this paper is the study of literature and the exploration of thought about empirical facts. In state relations and business development in the perspective of spatial political economy. The conclusion of the paper contains 4 ideas which are related to laying a strong economic foundation with a high level of community participation, economic democracy is expected to be an alternative solution in placing the role and function of business development, economic democracy can minimize horizontal conflict, and equitable access and availability of infrastructure is even between regions.